(untitled) (International Conference on Computers in Education, 2016)
Troubleshooting is an important ability to required by Computer Science undergraduates. The current research work tries to teach troubleshooting as a skill using a technologically enabled smart learning environment. This proposal gives an overview of the literature related to teaching troubleshooting, the instructional strategy of the learning environment and a plan to evaluate the learning environment.